A 30-Minute Video Documentary on COVID-19 Pandemic and Teaching-Learning Effectiveness in Selected Universities in Kwara State, Nigeria - ARUWA Joel Eleojo; ONAKPA Mohammed Shaibu, Ph.D.; OTTAH Alhassan Gabriel, Ph.D.; ALIYU-OHIARE Fati (Covenant Journal of Communication, 2024)
COVID-19 Pandemic posed significant challenges on education especially in a developing country such as Nigeria; schools without the necessary facilities to take online classes suffered greatly. This dissertation was based on COVID-19 pandemic: its impacts on education through the use of television documentary. The general objective of this study is to find out the impact of COVID-19 on education particularly the secondary and tertiary institutions in Nigeria. Diffusion of innovation theory as well as social cognitive theory were adopted in this study. This documentary serves as an eye opener to the menace in the public institution and the efforts of the private institution regarding online teaching and learning. Therefore, government at all levels should as a matter of concern work together to boost education in Nigeria for a better human development, it is also recommended that government should improve on the budget for education sector, ensure that, it is channeled through the right source for effective development while making sure that computer based centre are built across all schools with close monitoring and proper maintenance. University Students at all levels should be encouraged to embrace the online form of learning.